Formulation and evaluation of flunarizine-loaded spanlastic nanovesicles for treating migraine - Haiss, Mahmood A.; Abd Alhammid, Shaimaa N. (Pharmakeftiki, 2025)
This study investigates the use of spanlastic nanovesicles in order to enhance the solubility and bioavailability of flunarizine. Flunarizine-loaded spanlastics were prepared using the ethanol injection method, and were subsequently evaluated for particle size, polydispersity index, zeta potential, entrapment efficiency, and deformability index. The optimized formulation exhibited a particle size of 185 nm, a polydispersity index of 0.2134, a zeta potential of -17 mV, an entrapment efficiency of 68.01%, and a relative deformability of 8.32 g. The findings support spanlastic nanovesicles as a viable delivery system for improving the solubility and enhancing the bioavailability of flunarizine.